Dynamics of Giving Traditional Degree Children on Khatam Al-Quran at Minangkabau - Helfi; Hendri (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
The background of this research is that in Minangkabau, boys and girls must be good at reading the Koran. This is marked by the khatam of the Qur'an and the awarding of customary titles. but the granting of the customary title violates the general provisions. conception according to adat in Minangkabau. So the purpose of this research is to find out the process of giving customary titles to children, knowing the differences and the history of giving traditional titles to children khatam Al-Quran in Minangkabau. This research includes field research by gathering information through observation, in-depth interviews with predetermined informants. From the results of research on giving customary titles to children who graduate from the Qur'an by deliberation between mamak and bako. the title is announced or before or after the khatam qur'an celebration. the privilege of giving customary titles to them is to glorify children and is a form of traditional and religious ties. There are 2 versions of the origin of giving customary titles to children of khatam quran in Minangkabau. namely the event of the padri war and the event of the hill marapalam oath of sati